Review of Arthur R. Kroeber’s “China’s Economy: What Everyone Needs to Know” - Rubaj, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The process of political and economic reform in China was initiated just after the death of the leader of the Chinese Communist Party, Mao Zedong, in 1976. Understanding past and current reality of this country is difficult as its economic and political system is somewhere between a bureaucratic and authoritarian one-party state and a market-orientated modern economy. Over the last three decades, China has joined the ranks of world leaders in the political, economic and military spheres. Arthur R. Kroeber’s China’s Economy: What Everyone Needs to Know examines China’s transformation in the 20th and 21st centuries and the country’s current position in the global economy. Kroeber discusses past reforms, the long-term economic and social development that has transpired in recent decades and future problems the authorities and society will face in coming years.